Pendampingan Pemanfaatan Sampah Menjadi Loose Part Sebagai Media Pembelajaran Diferensiasi Anak Usia Dini - Ummah, Nahdiyatul; Oviani, Mila; Wardhani, Jihan Kusuma (At Taawun Bangun Bangsa, 2025)
This study examines an educational mentoring program on utilizing waste as loose parts in differentiated learning for early childhood education at RA Miftakhul Hikmah Mojosari. The background of this study lies in the limited creativity of teachers in implementing differentiated learning, mainly due to restricted learning media. Additionally, inorganic waste is often directly transferred to waste banks without optimal utilization, despite its potential as an affordable and environmentally friendly educational resource. This mentoring program was conducted using a service-learning method with a direct service approach. Teachers actively implemented learning activities at RA Miftakhul Hikmah while receiving guidance from service-learning supervisors. The strategy consisted of three stages: preparation (including observation, interviews, curriculum material development, and learning strategy design), implementation (utilizing recycled materials as educational play tools), and evaluation (assessing the outcomes of the mentoring program). The results indicate that loose parts derived from plastic waste, bottles, cardboard, and bottle caps can be effectively used as constructive, sensory, and numeracy learning media. Children showed higher enthusiasm during learning activities, while teachers demonstrated increased creativity in designing differentiated instruction. In conclusion, the utilization of waste as loose parts is effective in improving learning quality and fostering environmental awareness among early childhood learners.